Role of Swallowing Function of Tracheotomised Patients in Major Head and Neck Cancer Surgery. Issue 2 (March 2018) - Bartella, Alexander K.; Kamal, Mohammad; Berman, Sean; Steiner, Timm; Frölich, Dirk; Hölzle, Frank; Lethaus, Bernd
Abstract : Introduction: Tracheotomy is a frequent procedure in extended head and neck cancer surgery and known to be a risk factor for prolonged hospitalization. The authors hypothesized that the clinical course and delayed decannulation of patients are not only influenced by airway narrowing, but also by a compromised postoperative swallowing function. Material and Methods: The investigators implemented a retrospective cohort study. The sample was composed of a tertiary care center patients who underwent major head and neck cancer surgery, each receiving a tracheostomy. Data collected include general clinical data as well as endoscopical evaluation of swallowing function and aspiration rate. Descriptive and bivariate statistics were computed and the P value was set at.05. Results: The sample was composed of 96 patients with an average age of 64.2 and sex ratio of 1.4:1 (m:f). There was a strong statistically significant relation between swallowing function and timing of decannulation ( P < 0.001) and duration of hospitalization ( P < 0.001). Age ( P = 0.55), sex ( P = 0.54), tumor size ( P = 0.12), general diseases ( P = 0.24), distant metastases ( P = 0.15), or extent of neck dissection ( P = 0.15) were not significantly associated to swallowing function. Permanent cannulation was significantly correlated to a primary cancer of the soft palate or base of the tonge ( P < 0.001). Conclusion: The results of this study confirm the importance of the evaluation of swallowing function before the removal of the tracheotomy cannula in head and neck cancer patients.